Outcome of Initial Endodontic Treatment Performed, by One Specialist, in 122 Tunisian Patients: A Retrospective Study - Latifa Berrezouga; Adel Bouguezzi; Mohamed Semir Belkhir (International Journal of Dentistry)
Objective. To assess the 6- to 24-month outcome of endodontic treatments performed, by one specialist, and to identify prognostic factors that may influence initial endodontic treatment outcome (IETO). Methods. One hundred and forty-six patients out of 163 were included. A number of 201 teeth were endodontically treated, and an overall number of 408 canals were obturated. Of these, 165 teeth received initial endodontic treatment (IET). The criteria of the European Society of Endodontology were used to assess the IETO. The level of significance was set at p<0.05%. Results. Apical periodontitis (AP) was present in 42.5% of all cases, with a PAI >3 in 28.5%. The success rate (SR) was 91.5%. It was significantly higher in vital teeth (97%) than in devital teeth (87.7%) (p=0.04); however, a lower SR was recorded in teeth with AP (p=0.02). The lesion healed in 60 teeth (85.7%), decreased in size in 4 teeth (5.7%), and increased in size in 6 teeth (8.5%). A higher SR was obtained when a permanent restoration was present (94%) than absent (68.7%) (p=0.005). Conclusion. Within the limitations of the study, pulp and periapical status and permanent restoration are found to be strong outcome predictors.